79: Hypoglycemia in Full-Term Newborns with No Pre-Identified Risk Factors. Issue 6 (1st June 2014) - Flavin, M; Grewal, K; Hu, L
Abstract: BACKGROUND: Monitoring protocols are used for early detection of hypoglycemia in at-risk term newborns such as infants of diabetic mothers, those with growth restriction or macrosomia and infants with acute neonatal illness. Universal glucose monitoring is not recommended since benign transient hypoglycemia occurs in up to 14% of healthy term newborns. Clinically significant hypoglycemia is felt to be uncommon in newborns with no known risk factors. However, unmonitored newborns who do become hypoglycemic often have a delay in diagnosis and treatment as onset of symptoms may be the indication to measure blood glucose. OBJECTIVES: To determine the prevalence of significant hypoglycemia amongst full term newborns with no pre-identified risk factors in a regional centre. DESIGN/METHODS: We reviewed the charts of newborns born at 37 to 42 weeks, birthweight 2500 g to 3999 g with documented hypoglycemia at a regional centre over a three year period. We focussed on those with a glucose level of <2.0 mmol/L and requiring IV dextrose. Infants of mothers with gestational and pre-gestational diabetes were excluded as were infants with birth depression, transient respiratory distress and those with acute illness. RESULTS: From a population of 6272 term newborns we identified eight hypoglycemic infants who met the criteria. Four of the newborns were less than the10th centile for weight and one baby had Down Syndrome. Of the remaining three hypoglycemic infants the first presented at 26 h of life with jitteriness. Blood glucose was 1.3 mmmol/L. Hypoglycemia resolved three days later. Polycythemia was noted. Mother was obese and hypertensive. The second case presented with jitteriness at 60 h of life with blood glucose 1.5 mmol/L. Hypoglycemia resolved a day later. No diagnosis was made. Mother was obese. The third case presented at 13 h with jitteriness and blood glucose 0.3 mml/L. He subsequently had three seizures. Hypoglycemia resolved six days later. The diagnosis was transient hyperinsulinism. Mother was hypertensive. CONCLUSIONS: Use of <10th centile weight parameter, as recommended by the CPS, is superior to an arbitrary weight cut-off in identifying growth-restricted term newborns who may be at risk of hypoglycemia. A small number of normal birth weight newborns fall outside current monitoring recommendations yet have clinically significant hypoglycemia. Many of these infants do not have a chronic underlying metabolic or endocrine disorder. We recently launched a Canadian Pediatric Survellance Program project to determine incidence of hypoglycemia in term newborns without pre-identified risk factors, to document presentation and early morbidity and to obtain clues about unrecognized or underappreciated risk factors.